2017
DOI: 10.1002/2017ja024836
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Periodicities During the Cassini Grand Finale

Abstract: The Cassini F ring and Proximal orbits took the spacecraft closer to Saturn than any previous mission and allowed determination of energetic charged particles (E > 20 keV) in the inner magnetosphere of the planet. The periodicities of the energetic electrons show a remarkable consistency when analyzed using Lomb periodograms. From the beginning of the F ring orbits in October 2016 to the end of the mission in September 2017, the particles manifest a strong main period of 10.79 h ± 0.01 h, with small Doppler‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
(83 reference statements)
3
6
0
Order By: Relevance
“…These values are very close to those attained by mid-2015 after the interval of period coalescence at 10.66 hr between mid-2013 and mid-2014 and subsequent period reversal Ye et al, 2016). Consistent with these results, Carbary et al (2017) have also reported energetic electron modulations during the F ring and proximal orbit intervals with a near-constant period of 10.79 ± 0.01 hr, as observed most clearly in northern hemisphere data. However, they did not detect the southern system period in either southern or northern hemisphere electron data.…”
Section: 1029/2018ja026079supporting
confidence: 88%
“…These values are very close to those attained by mid-2015 after the interval of period coalescence at 10.66 hr between mid-2013 and mid-2014 and subsequent period reversal Ye et al, 2016). Consistent with these results, Carbary et al (2017) have also reported energetic electron modulations during the F ring and proximal orbit intervals with a near-constant period of 10.79 ± 0.01 hr, as observed most clearly in northern hemisphere data. However, they did not detect the southern system period in either southern or northern hemisphere electron data.…”
Section: 1029/2018ja026079supporting
confidence: 88%
“…The energetic electron periodicities during 2016/2017 exhibit a very similar dominant period associated with the northern hemisphere. This is approximately equal to the summer southern hemisphere period from earlier in the Cassini mission (Carbary et al, 2017). showed the amplitude of the equatorial azimuthal field component varied with radial distance and local time with the nightside amplitude being~2 times larger compared to the dayside at 10 R S .…”
Section: Introductionmentioning
confidence: 76%
“…The PPOs are present in many of the magnetospheric observations, namely, radio and magnetic field measurements, plasma data, and auroral emissions, and act to modulate the behavior of the magnetosphere (e.g., Carbary et al, 2017;Carbary & Mitchell, 2013;Jackman et al, 2016;Ramer et al, 2017;Thomsen et al, 2017;Ye et al, 2016). The PPOs are present in many of the magnetospheric observations, namely, radio and magnetic field measurements, plasma data, and auroral emissions, and act to modulate the behavior of the magnetosphere (e.g., Carbary et al, 2017;Carbary & Mitchell, 2013;Jackman et al, 2016;Ramer et al, 2017;Thomsen et al, 2017;Ye et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that Saturn's internal magnetic field is highly symmetric with respect to its rotational axis (Burton et al, ), rotational modulation has been observed in Saturn radio emissions, magnetic field perturbations, charged particles, energetic neutrals, and motions of the plasma sheet, auroral oval, and magnetopause (Desch & Kaiser, ; Espinosa & Dougherty, ; Espinosa et al, ; Gurnett et al, ; Carbary et al, ; Paranicas et al, ; Andrews et al, ; Andrews, Coates et al, ; Andrews et al, ; Clarke, Andrews, Arridge et al, ; Clarke, Andrews, Coates et al, ; Nichols et al, ; Khurana et al, ; Provan et al, , ; Carbary & Mitchell, , and references therein; Carbary et al, ). A period very close to the modulation period of Saturn kilometric radiation (SKR) was originally adopted by the IAU as the rotation period of Saturn (10.656 hr) due to the lack of a trackable solid surface on the gas giant.…”
Section: Introductionmentioning
confidence: 99%